Propuesta de Control de Inventarios 5 “S” Japonesas en Comercial “Mil Maravillas” de Cabrera Medina Nury del Cisne, Ciudad de Loja - Quille Naikiai, Erik Xavier (2024)
This research work aims to implement a system of inventory control called "5 S Japanese" in a commercial establishment in the city of Loja, "Mil Maravillas", managed by Mrs. Cabrera Medina Nury del Cisne, developed for the purpose of obtaining a degree in accounting and auditing. Based on the objectives of the degree work, an internal control questionnaire was conducted to identify the characteristics, advantages and disadvantages of inventory management, finding that the company does not conduct a physical inventory taking. This led to developing an inventory detailing the quantity, category, unit cost and total cost of each of the products that are in stock, allowing to have an organized and detailed record that gave way to implementing this proposal. Following the development of a schedule based on the activities involved in implementing the Japanese 5 S methodology, it was determined to specify the task, the responsible individual, and any observations that arise during each phase of the method, such as Seiri (classifying), Seiton (organizing), Seiso (cleaning), Seiketsu (standardizing) and Shitsuke (discipline), in order to separate items that are available for sale from items that have distinctive characteristics preventing their sale. Subsequently, all the items were organized according to their rotation and demand, for which the company's space was divided into specific areas. Cleaning activities and the creation of standards were implemented so that the members of the company could carry out the activities proposed in daily operations. Finally, evaluations of compliance with the established standards were carried out and the methodology was disseminated through a poster, so that employees understand and adopt the practices of this methodology. The manager-owner of the company is also presented with an implementation proposal for the implementation of an inventory control system that will assist in improving the organization, rotation, location, and handling of merchandise, contributing to the organization's economic and operational growth.